PENGARUH PENGGUNAAN TEPUNG BULU AYAM TERFERMENTASI SEBAGAI PENGGANTI KONSENTRAT DALAM RANSUM TERHADAP KECERNAAN PROTEIN DAN BETN TERNAK BABI - DALLE N. S.; TUKAN H. D. (Fakultas Peternakan Universitas Udayana, 2022)
The study aimed to evaluat effect of including fermented feather meal (FFM) in basal diet as substitution of concentrate KGP-709 on digestibility protein and BETN of starter pigs. There were 16 landrace crossbred pigs 2-3 months old with 6-19 kg (average 13.59 kg; CV= 29.59%) initial body weight used in the study. Trial method used is a method experiment and used complete block design 4 treatments with 4 replicates procedure was applied in the study. The 4 treatment feeds were formulated as: R0: basal diet with 100% concentrate without FFM (control); R1:basal diet with 90% concentrate + 10% FFM; R2: basal diet with 80% concentrate + 20% FFM; and R3: basal diet with 70% concentrate + 30% FFM. Variables evaluated were: intake basal diet, intake protein, digestibility pro- tein, intake BETN and digestibility BETN. Statistical analysis shows there were not significant (P>0.05) on research variable but gave elatively the same effect on each treatment. Concluded in this reaserch is concentrate KGP-709 in the diet could be replaced with FFM because it gave relatively the same results as the control.